Cohort Effect on Well-Being: The Legacy of Economic Hard Times - Sutin, Angelina R. (2013)
The present research examines the effect of age, cohort, and time of measurement on well-being across adulthood. Cross-sectional and longitudinal analyses of two independent samples – one with >10,000 repeated assessments across 30 years (Assessments per participant: M =4.44, SD=3.47) and one with nationally representative data – suggested that well-being declines with age. This decline, however, reversed when we controlled for birth cohort. That is, once we accounted for the fact that older cohorts had lower levels of well-being, all cohorts increased in well-being with age relative to their own baseline. Participants tested more recently had higher well-being, but this time of measurement effect did not change the shape of the trajectory as did cohort. Although well-being increased with age for everyone, cohorts that lived through the economic challenges of the early 20(th) century had lower well-being than those born during more prosperous times.